Implementation of Sociocultural Education in Facing The Industrial Revolution 4.0 in Madrasah Aliyah (MA) NW Pancor - Mispandi Mispandi; Ani Widayati (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: This study aims to find out how the implementation of sociocultural education in the face of the industrial revolution era 4.0 in the Aliyah NW Pancor Madrasah. This study uses qualitative research with trigulation data collection techniques (a combination of observation, interviews, and documentation). Data analysis uses descriptive analysis. The results showed that the Sociocultural Values ​​in the Aliyah NW Pancor Madrasah were implemented in learning activities, both intracuricular and extracurricular activities. In intracuricurer activities, sociocultural values ​​are used as an approach by teachers by implementing sociocultural-based learning systems, while in extracurricular activities, these values ​​are inserted in the form of Islamic arts and culture. Sociocultural education creates a harmonious relationship between madrasa residents, both teachers, students, madrasah stap and gives birth to values ​​of tolerance and culture, such as respecting cultural differences and regional languages. the results of the study also showed that education carried out at the Aliyah NW Pancor Madrasah, at least touched three dimensions namely, the spiritual dimension of the culture and local languages, the social dimension between the madrasa residents, and the professional dimension. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana implementasi pendidikan sosiokultural dalam menghadapi era revolusi industri 4.0 di Madrasah Aliyah NW Pancor. Penelitian ini menggunakan penelitian kualitatif dengan teknik pengumpulan data secara trigulasi (gabungan observasi, wawancara, dan dokumentasi). Analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa Nilai-Nilai sosiokultural di Madrasah Aliyah NW Pancor yang diimplementasikan dalam kegiatan pembelajaran, baik kegiatan intrakurikuler maupun ekstrakurikuler. Dalam kegiatan intrakurikurer, nilai sosiokultural digunakan sebagai pendekatan oleh guru dengan mengimplementasikan sistem pembelajaran berbasis sosiokultural, sedangkan dalam kegiatan ekstrakurikuler, nilai tersebut disisipkan dalam bentuk kesenian islam, dan budaya. Pendidikan sosiokultural menciptakan hubungan harmoni antar warga madrasah, baik guru, siswa, stap madrasah dan melahirkan nilai toleransi dan budaya, seperti menghargai perbedaan budaya dan bahasa daerah. Hasil penelitian juga menunjukkan bahwa pendidikan yang dijalankan di Madrasah Aliyah NW Pancor, setidaknya telah menyentuh tiga dimensi yaitu, dimensi spiritual budaya dan bahasa daerah, dimensi sosial antar warga madrasah, dan dimensi professional.